Peran Pendidikan Agama Islam dalam Membentuk Karakter Siswa di Era Globalisasi - Tantika Tri Hapsari; Marenza Agus; Haerlini Puspika Sari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to examine the role of Islamic Religious Education (PAI) in the formation of students' character in the era of globalization which is full of value challenges due to technological developments and information flows. Globalization has had a significant impact on the morality of the younger generation, so that religious-based character education is becoming increasingly important. Using a qualitative research method based on literature studies, data were collected from various relevant scientific literature sources and analyzed thematically. The results of the study indicate that PAI plays a central role in instilling students' faith, morality, and social values ​​through value-based learning, habituation of worship, and teacher role models. However, globalization is a contextual factor that can weaken or strengthen this influence depending on the implementation strategy. These findings strengthen Lickona's character education theory and Bandura's social learning theory, and show the importance of an adaptive and contextual approach in teaching PAI. The implications of this study are the need to develop a more innovative, integrative, and collaborative PAI curriculum and learning strategy between schools, families, and communities so that religious values ​​remain firmly embedded in students amidst the challenges of globalization.